2007
DOI: 10.1038/sj.jp.7211803
|View full text |Cite
|
Sign up to set email alerts
|

Extremely low birth weight infants are at high risk for auditory neuropathy

Abstract: Auditory neuropathy (AN) is a condition in which transmission of sound to the brain is abnormal. This is reflected as an electrophysiologic profile of normal otoacoustic emissions (OAE), with abnormal auditory brainstem evoked responses (ABR). Functionally speech perception is impaired and management strategies remain controversial. AN can be missed if high-risk newborns are screened for hearing loss with only OAE testing. The rate of sensorineural hearing loss (SNHL) in high-risk nursery infants is 10 times g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
51
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 31 publications
6
51
1
3
Order By: Relevance
“…These differences between the selective IHC loss group and both other groups were statistically significant (pG 0.05 by unpaired t test). These data mirror those of a recent clinical study finding that infants with AN showed, on average, 4-week shorter gestation periods than those with other forms of sensorineural hearing loss (Xoinis et al 2007). …”
Section: Full-term Casesupporting
confidence: 88%
See 4 more Smart Citations
“…These differences between the selective IHC loss group and both other groups were statistically significant (pG 0.05 by unpaired t test). These data mirror those of a recent clinical study finding that infants with AN showed, on average, 4-week shorter gestation periods than those with other forms of sensorineural hearing loss (Xoinis et al 2007). …”
Section: Full-term Casesupporting
confidence: 88%
“…The high percentage of ears with hair cell loss of all types is perhaps not surprising given that sensorineural hearing loss is significantly more common in NICU survivors than in babies not requiring such intense hospital care at birth (Xoinis et al 2007) and that the ears analyzed here were from the population that was so seriously ill that they did not survive the NICU stay. Although many of these infants with various forms of sepsis may have been treated with aminoglycosides, such treatment is not highly correlated with hearing loss in NICU survivors (Hess et al 1998).…”
Section: The Known Causes Of Selective Ihc Lossmentioning
confidence: 79%
See 3 more Smart Citations